Analisis Produk UMKM Sektor Makanan Kota Mataram Pada Aspek Loyalitas Pelanggan (Studi Pada Produk Tahu Abian Tubuh) - Ilhamudin, Muhammad; Hilmiati, Hilmiati; Rusminah, Rusminah (Universitas Mataram, 2024)
This study aims to assess customer loyalty toward Abian Tubuh tofu, one of Mataram City's flagship products. Using a descriptive research approach, the study seeks to provide insights into customer loyalty, a key aspect of consumer behavior theory. A sample survey method was employed, selecting several tofu markets in Mataram City as research locations. The population includes all customers who purchase tofu at these markets, with purposive sampling used to select respondents based on the research objectives. Given the unknown total population, a sample of 100 respondents was determined. The analysis utilized the Net Promoter Score (NPS) model to measure and understand customer loyalty levels. This study builds upon previous research focusing on the same product, Abian Tubuh tofu, in Mataram. Customer loyalty, a critical aspect of consumer behavior, needs periodic evaluation to ensure continued purchases and customer retention. Findings indicate that customers are highly loyal to Abian Tubuh tofu, based on various product attributes such as taste, price, aroma, texture, and nutritional content. The strong perception of product quality leads customers to recommend it to friends and colleagues. Marketers should maintain and enhance this level of loyalty to ensure business sustainability in the future.